Campaign Finance Bills, 106th Congress : Comparison of Shay's Meehan & McCain-Feingold Proposals. (U.S. Congressional Research., 1999)
Provides a side-by-side comparison of campaign finance reform provisions in H.R. 417 (Shays-Meehan) and S. 26 (McCain-Feingold).